Children as controls in research; The voice of the volunteer - Oskar W. Angenete; Janne Haustreis; Lisbeth K. Aune; Anette Lundestad; Lena Cetrelli; Thomas Angell Augdal; Ellen Berit Nordal; Kjersti Grønning; Marite Rygg (PLoS ONE, 2025)
Background Modern paediatric healthcare is increasingly dependent on diagnostic methods such as imaging and blood samples. These methods require knowledge of physiology and anatomy to separate signs of early disease development from physiological variants. To acquire this knowledge, researchers depend on studies on children from the general populations, but little is known about how children and their guardians experience participation in studies. This study aims to map the experiences of children participating in research. Materials and methods From a cohort of children and guardians from the general population, participating as controls in a large study on juvenile idiopathic arthritis (NorJIA), a subset was invited to share their experiences. The participants were examined using blood sampling, MRI, x-ray, bone-density scan, anthropometric measurements, and questionnaires. A questionnaire of 26 questions regarding their experiences from the study was sent out 2–4 weeks after the data collection. Results The questionnaire was filled out by 50 children and 50 guardians. A large majority of the children responded that they were positive to help researchers, that blood sample procedures and imaging procedures went well, that they would participate in the study again, and would recommend their friends to take part in similar studies. Guardians generally responded positively, but there were diverging responses between children and guardians. Conclusion Children from the general population reported mainly positive experiences from participation in research, including imaging and blood sampling. The experiences of the children and their guardians are sometimes diverging, underpinning the importance of addressing the child’s opinions.